Identifying optimal clinical trial candidates for locoregionally advanced nasopharyngeal carcinoma: Analysis of 9468 real-world cases and validation by two phase 3 multicentre, randomised controlled trial. (February 2022) - Tang, Si-Qi; Chen, Lei; Li, Wen-Fei; Chan, Anthony T.C.; Huang, Shao Hui; Chua, Melvin L.K.; O'Sullivan, Brian; Lee, Anne W.M.; Lee, Nancy Y.; Zhang, Yuan; Chen, Yu-Pei; Xu, Cheng; et al.
Highlights: N2-3 or T4 patients were ideal candidates for locoregionally advanced NPC trials. Patients with pre-treatment EBV DNA ≥4, 000 copies/mL might be eligible for trials. Patients with detectable post-treatment EBV DNA are candidates for adjuvant trials. Abstract: Background and purpose: This study aims to identify the optimal high-risk candidates for clinical trials in locoregionally advanced nasopharyngeal carcinoma (NPC). Materials and methods: Non-metastatic NPC patients ( n  = 9, 468) were included. Recursive partitioning analyses (RPA) were performed to generate risk stratification. Receiver operating characteristics curve was used to determine the cut-off value of pre-treatment Epstein-Barr virus (EBV) DNA for progression-free survival (PFS). Individual-level data from two clinical trials were used for validation. Results: Anatomic stratification based on T and N category (eighth edition TNM, TNM-8) classified the N2-3 or T4 as an anatomic high-risk group with 5-year PFS of 69% (95% confidence interval: 68–71%). Prognostic stratification identified patients with pre-treatment EBV DNA ≥4000 copies/mL as a prognostic high-risk group with 5-year PFS of 69% (67–70%). The c-index was significantly higher for anatomic stratification (0.621, p  < 0.001) and prognostic stratification (0.585, p  < 0.001) compared with existing TNM-8 stage groups (0.562). The validation cohorts based on clinical trials data showed greater PFS benefit than the results of the original trials [Hazard ratio: NCT01245959, 0.64 vs. 0.67; NCT01872962, 0.42 vs. 0.52]. Moreover, detectable post-treatment EBV DNA indicated a high risk of progression with 5-year PFS of 38.7% and was the most adverse independent factor for all endpoints. Conclusions: N2-3 or T4 NPC patients were ideal candidates for multicenter clinical trials in locoregionally advanced NPC. Patients with detectable post-treatment EBV DNA are suitable candidates for adjuvant trials.